The role of english pre-service teachers’ beliefs about teaching in teacher education programs (2013)
This paper presents a review of studies on pre-service teachers’ beliefs about teaching. The purpose of the article is to show teacher educators the relevance of exploring such issue in the classroom. Preservice teachers come into the teaching profession with beliefs about teaching; sometimes they are aware of them, other times they are not. The studies reviewed in this paper demonstrate that when teacher educators ascertain this principle, they clearly integrate it in their syllabi thus aiding preservice teachers to acquire awareness of their entering beliefs about teaching and to experience changes in them so that explicit beliefs guide and inform the act of teaching. Teacher educators assist this process through reflection, course content, and learning activities, as well as by engaging in researchactivities.En este artículo se presenta una revisión de varios estudios sobre las creencias de los docentes en formación acerca de la enseñanza. El propósito es mostrar a los educadores de docentes en formación la relevancia de explorar este tema en el salón de clase. Los profesores en formación entran a laprofesión docente con creencias acerca de la enseñanza; algunas veces son conscientes de estas, otras veces no. Los estudios aquí citados demuestran que cuando los educadores de docentes en formación asumen este principio, lo integran claramente en el currículo, y de este modo ayudan a los docentes en formación a ser conscientes de sus propias creencias iniciales y a transformarlas, de tal forma que les guíen e informen acerca de su labor pedagógica. Los educadores apoyan este proceso por medio de la reflexión, los contenidos, las actividades de aprendizaje y las actividades investigativas.